2022
DOI: 10.1186/s12940-022-00912-5
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature-related mortality and associated vulnerabilities: evidence from Scotland using extended time-series datasets

Abstract: Background Adverse health impacts have been found under extreme temperatures in many parts of the world. The majority of such research to date for the UK has been conducted on populations in England, whilst the impacts of ambient temperature on health outcomes in Scottish populations remain largely unknown. Methods This study uses time-series regression analysis with distributed lag non-linear models to characterise acute relationships between dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
3
18
0
1
Order By: Relevance
“…Consistent with the existing literature e.g., [3,6,11,19,57,78,[85][86][87][88][89][90], this work demonstrated that older people are particularly prone to non-optimum temperatures, which probably stems from the decreasing with age ability of thermoregulation, along with co-existing health problems and socioeconomic factors including low income and isolation [37,[91][92][93]. Specifically, our results showed that extremely high and secondarily extremely low temperatures put the highest risk of cardiorespiratory mortality for the elderly, while the largest burden of mortality was attributed to moderate cold.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the existing literature e.g., [3,6,11,19,57,78,[85][86][87][88][89][90], this work demonstrated that older people are particularly prone to non-optimum temperatures, which probably stems from the decreasing with age ability of thermoregulation, along with co-existing health problems and socioeconomic factors including low income and isolation [37,[91][92][93]. Specifically, our results showed that extremely high and secondarily extremely low temperatures put the highest risk of cardiorespiratory mortality for the elderly, while the largest burden of mortality was attributed to moderate cold.…”
Section: Discussionsupporting
confidence: 88%
“…A large number of works have demonstrated that females are more vulnerable to thermal stress e.g., [14,43,78,83,93,101], while others have found more pronounced effects for males e.g., [6,19]. Recent work for Scotland concluded that low temperatures affected males more, while females were more afflicted by high temperatures [90]. Similarly, a study focused on Spain [89] reported a higher risk of heatrelated CVD mortality for females, whereas males were found more vulnerable to low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has already proven a significant connection between ambient temperature and respiratory disease mortality. A study from Mianyang City found that the exposure–response curve between daily mean temperature and mortality from respiratory diseases showed a "V"-shaped nonlinear feature, with both cold and hot temperatures increasing the risk of mortality from respiratory diseases [ 40 ], and its findings were similar to those of several other studies [ 13 , 25 , 41 , 42 ]. However, there are limitations in the investigation of the relationship between ambient temperature and mortality.…”
Section: Discussionsupporting
confidence: 76%
“…The lag days for cold spells were adjusted from 0–21 days to 0–30 days. Furthermore, we incorporated single air pollutants (NO 2 , CO, and SO 2 ) as well as combined air pollutants (PM 2.5 &NO 2 , PM 2.5 &SO 2 , and PM 2.5 &NO 2 &SO 2 ) into the model separately to explore the impact of confounding factors on the results [ 31 ], [ 32 ].…”
Section: Methodsmentioning
confidence: 99%